Investigação da interação entre a haste de uma colhedora e o ramo de um cafeeiro utilizando modelagem computacional - Souza, Victor Hugo Silva (2017)
In the past, a validation of problem solving in the industry was obtained, almost entirely, through experimental testes. Currently there is no new product development. Considered as difficulties to model biological structures, such as the coffee branch, the objective of this work was evaluated by the mechanical behavior of the interaction between a stem of the harvester and the coffee branch by vibration, using computational modeling. To do this, perform a model of the harvester platform and the coffee branch through commercial software Solidworks ® and subsequent numerical simulations via the Finite Element Method for analysis of stresses and displacements without Ansys ® software version 14.5. Experimental tests were carried out from samples of a stem of a harvester and with coffee tree branches of Catuaí Vermelho variety IAC 144, with no intention to validate the results of the numerical simulations. Results found in the simulation for the displacement and acceleration were, respectively, 0.225 mm and 43.342 m/s². Already results were obtained in the experimental test for the displacement and acceleration of 0.293 mm and 41.982 m/s². With this, they were validated as numerical simulations, which may contribute to the direction of new scientific research, in the creation and development of new technologies for the mechanized coffee harvesting system, using computational modeling.